2019
DOI: 10.4274/tjcd.galenos.2019.50374
|View full text |Cite
|
Sign up to set email alerts
|

Type 4 Congenital Pouch Colon without Fistula with Anal Agenesis and Lower Vaginal Agenesis in a Female Fetus: A Rare Autopsy Case Report

Abstract: Konjenital poş kolon, kalın bağırsağın tamamının veya bir kısmının, genellikle bir fistül yoluyla ürogenital sistem ile bağlantı kuran, kese benzeri bir dilatasyon ile yer değiştiği bilinmeyen bir embriyogenezisin nadir bir anorektal bozukluğudur. Bu durum Kuzey Hint popülasyonundaki erkekler arasında daha yaygındır ve uterovajinal malformasyonlar gibi çeşitli anomalilerle ilişkilidir. Yıllar içinde tip 4 gibi daha az ciddi tiplere doğru kayma gösteren beş tipe ayrılmıştır. Otopsi sırasında tanı alan 29 haftal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…retrospective study was carried out which included 230 autopsy cases received at Department of Pathology, Hassan Institute of Medical were from 99 males and 28 females. Forty-one-60 years of age group was found to be most common.In the present study, we observed steatosis as most common liver lesion which correlated with other studies by Singh et al and Devi et al[18,19]. We observed vascular lesion as most common kidney lesion which was similar to the other studies.In a study conducted bySelvi et al., they found steatosis as most common liver pathology in liver autopsy specimens.…”
supporting
confidence: 92%
“…retrospective study was carried out which included 230 autopsy cases received at Department of Pathology, Hassan Institute of Medical were from 99 males and 28 females. Forty-one-60 years of age group was found to be most common.In the present study, we observed steatosis as most common liver lesion which correlated with other studies by Singh et al and Devi et al[18,19]. We observed vascular lesion as most common kidney lesion which was similar to the other studies.In a study conducted bySelvi et al., they found steatosis as most common liver pathology in liver autopsy specimens.…”
supporting
confidence: 92%